Modelo de intervención social y ambiente: el caso de algunos barrios antiguos de Xochimilco - del Roble Pensado Leglise, Mario; Alonso Reyes, María del Pilar; Bucio Yáñez, Rachel (El Colegio de México A.C., 2011)
This article examines the concept of the model of social intervention and its use in the solution of socio-environmental problems on the basis of the opinion surveys conducted in 2007 and 2008 in two neighborhoods in Xochimilco on the implementation of the “No More Garbage” program, designed to prevent the pollution of the lake channels. It concludes that the results were limited due to the persistence of pollution from rubbish and sewage in the canals and the presence of irregular settlements in the chinampa zone. The working hypothesis, corroborated by analytical instruments, posits that the alternative to this inefficient implementation is the establishment of a process of social intervention based on environmental education, whose main axis involves considering that the problem is not conducive to a good quality of life for the social group affected. This would activate their participation in order to achieve an effective solution to this socio-environmental problem.